Health service utilization and direct healthcare costs associated with obesity in older adult population in Ghana - Stella T Lartey; Barbara de Graaff; Costan G Magnussen; Godfred O Boateng; Moses Aikins; Nadia Minicuci; Paul Kowal; Lei Si; Andrew J Palmer (Oxford University Press, 2022)
Obesity is a major risk factor for many chronic diseases and disabilities, with severe implications on morbidity and mortality among older adults. With an increasing prevalence of obesity among older adults in Ghana, it has become necessary to develop cost-effective strategies for its management and prevention. However, developing such strategies is challenging as body mass index (BMI)-specific utilization and costs required for cost-effectiveness analysis are not available in this population. Therefore, this study examines the associations between health services utilization as well as direct healthcare costs and overweight (BMI ≥25.00 and <30.00 kg/m2) and obesity (BMI ≥30.00 kg/m2) among older adults in Ghana. Data were used from a nationally representative, multistage sample of 3350 people aged 50+ years from the World Health Organization's Study on global AGEing and adult health (WHO-SAGE; 2014/15). Health service utilization was measured by the number of health facility visits over a 12-month period. Direct costs (2017 US dollars) included out-of-pocket payments and the National Health Insurance Scheme (NHIS) claims. Associations between utilization and BMI were examined using multivariable zero-inflated negative binomial regressions; and between costs and BMI using multivariable two-part regressions. Twenty-three percent were overweight and 13% were obese. Compared with normal-weight participants, overweight and obesity were associated with 75% and 159% more inpatient admissions, respectively. Obesity was also associated with 53% additional outpatient visits. One in five of the overweight and obese population had at least one chronic disease, and having chronic disease was associated with increased outpatient utilization. The average per person total costs for overweight was $78 and obesity was $132 compared with $35 for normal weight. The NHIS bore approximately 60% of the average total costs per person expended in 2014/15. Overweight and obese groups had significantly higher total direct healthcare costs burden of $121 million compared with $64 million for normal weight in the entire older adult Ghanaian population. Compared with normal weight, the total costs per person associated with overweight increased by 73% and more than doubled for obesity. Even though the total prevalence of overweight and obesity was about half of that of normal weight, the sum of their cost burden was almost doubled. Implementing weight reduction measures could reduce health service utilization and costs in this population.